The normative and values dilemmas related to the government-citizen relationship during the pandemic [Articol] - Ciobanu, Rodica; Roșca, Mariana (PRO Universitaria Publishing House, 2021)
The article outlines a part of the research findings carried out using a complex methodological framework, designed to assess the current social context of the Republic of Moldova, and aims to identify the governance modernization challenges. It reflects the assessment of the relationship between authorities and citizens during the pandemic crisis and demonstrates the relevance of value-normative foundations for the social construction. The preference for interdisciplinary methodology facilitated the structuring of the research in several basic compartments: the first one reflects in a synthetic formula the theoretical-methodological framework of analysis and the formulation of the working hypothesis, followed by the substantiation and support of the authors' positions on the basis of pragmatic and normative-value arguments, and concluded with generalizations that provide a platform for scientific debate with a view to pursuing further approaches on the subject of the impact of crises on the social framework and the need for spiritual foundations in human perpetuation. © 2021 PROUniversitaria Publishing House. All rights reserved.
Keywords: authorities; citizenship; government